Citrus Nutrition UF/IFAS Grower Trials - Tripti Vashisth; Jamie D. Burrow (EDIS)
Interested in learning more about citrus nutrition grower trials? This 2-page pamphlet provides information on the goals, objectives, benefits, and considerations of the trials, as well as specific information about trials being held from 2015-2017. The pamphlet also contains a sign up form for the trials. Written by Tripti Vashisth and Jamie D. Burrow, and published by the Horticultural Sciences Department, May 2016. Revised October, 2016.